Understanding the alternative work arrangement - Giordano, Frank (Kansas State University, 2023)
The alternative work arrangement, or work that deviates from employment under a single employer with consistent hours and location, has become a common form of employment due to its flexibility in hiring (Landsbergis et al., 2014; Kuhn, 2016), and has been rapidly growing (BLS, 2018; Statista, 2021). Prior research shows that there are reduced financial (Gash, 2008; Reichenberg & Berglund, 2019), health (Rousseau & Libuser, 1999), and well-being outcomes (Åkerblad, 2017) for those that predominantly engage in this type of work, with a potential for positive outcomes like freedom and flexibility (Friedman, 2014; Kuhn, 2016). The current research explores the utility of using proposed work features, Job Characteristics Theory, and Self-Determination Theory as a combined framework to meaningfully compare the alternative work arrangement to their traditional counterparts and other alternative work. Results replicate prominent differences across arrangements, such as alternative workers experiencing lower job security but higher autonomy than traditional workers. Alternative workers were also able to be parsed into four unique profiles based on the features within the combined framework. These results show that while there are broader differences between the alternative and traditional work arrangements, it is necessary to acknowledge their uniqueness. Specifically, certain work features such as flexibility, characteristics of the job, and motivational factors can contribute to understanding this uniqueness within the alternative work arrangement.
Keywords: Alternative; Gig; Temporary; Alternative work; Contract; Employment